UPAYA KARANG TARUNA ARMUBA DALAM MENINGKATKAN KEPEDULIAN SOSIAL DI DESA KARANGWALUH KECAMATAN SAMPUNG KABUPATEN PONOROGO - Utami, Wandha Yunia; Setyowati, Raden Roro Nanik (Kajian Moral dan Kewarganegaraan, 2024)
Karang Taruna is a forum for developing the social spirit of the younger generation in society. Social concern is defined as an attitude related to caring for others in the surrounding environment. This research aims to describe the efforts and obstacles of Karang Taruna Armuba in increasing social awareness in Karangwaluh Village, Sampung District, Ponorogo Regency. This research uses a descriptive qualitative research approach. Data collection techniques through observation, interviews and documentation. Data were analyzed using data collection, data reduction, data presentation, and drawing conclusions. The theoretical basis for this research is the social capital theory of philanthropy by Paul Schervish. The results of the research show that the efforts of Karang Taruna Armuba in increasing social awareness in Karangwaluh Village, Sampung District, Ponorogo Regency, namely through activities, 1) compensation activities, 2) social visits, 3) community service activities, 4) fooging activities, 5) day activities religious, 6) great youth training activities, 7) sports activities. Meanwhile, in implementing these efforts, there are different obstacles experienced by the youth of Karang Taruna Armuba in each activity that has been carried out. Keywords: Karang Taruna, Social Awareness, Efforts, Obstacles